UCS DUCS- SULAM - UiTM, UiTM Global (Office of International Affairs (OIA), 2024)
The semester 5 students from the Bachelor of Education Arts and Design, Faculty of Education, UITM showcased their work in eco-print crafts alongside distinguished delegates from Universitas Pendidikan Indonesia (UPI), Indonesia through the UCS DUCS-SULAM program in selected schools. This program connected classroom learning with real world practice, benefiting the community with students creativity, knowledge, and skills. At the same time, it promoted teamwork between students, teachers. and the global community.